School connectedness and Guatemalan youth substance use: Does gender matter? - Martinez, Marcos J.; Kawam, Elisa; Marsiglia, Flavio F.; Salas-Wright, Christopher; Ayers, Stephanie L.; Porta, Maria (Advances in Social Sciences Research Journal, 2016)
This study examined if school connectedness was protective for youth and if the effects of school connectedness on alcohol and cigarette/tobacco use varied by gender among a cross-sectional sample of Guatemalan youth (N = 322, Mage = 12.16, 53% male). Using Ordinary Least Squares regression, a significant inverse association was found between school connectedness and past 30-day alcohol use frequency (b = -.11, p < .01), past 30-day alcohol use amount (b = -.12, p < .01), past 30-day cigarette/tobacco use frequency (b = -.06, p < .05), and past 30-day cigarette/tobacco use amount (b = -.05, p < .10). A significant school connectedness by gender interaction effect was also found for all alcohol and cigarette/tobacco use outcomes. Although school connectedness appeared to be protective for youth, females had greater substance use once gender was accounted for. Findings are discussed further in relation to gender, youth prevention efforts and health.